A comparison of characteristics of high functional swimwear for competitive swimming - Gonjo, T.; Ichikawa, H.; Tsubakimoto, S.; Takagi, H. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The purpose of this study was to clarify factors of the high functional swimwears had made a lot of new world records recently, and to suggest design improvements for a new swimwear suitable for the new regulation by FINA. METHODS: Two elite swimmers participated in this study. LZR Racer (L), Aqua Force (F), and X-Glide (X), as the high functional swimwears, and Aile-Bleue (B) as a comparative swimwear were used. L has high wearing pressure, F was made by rubber, X has both peculiarity of L and F. To evaluate of characteristics of the swimwears, we measured 1) the passing velocity under the water after starting, 2) the cross sections (CS) of a leg, and 3) the passive drag by using a swim mill. RESULTS: The mean passing velocity (m/s) of the subjects after starting with the X was higher than others (X:2.1±0.5, L:2.0±0.4, F:2.0±0.4, B:1.9±0.5). The relative values (%) which indicate a constriction of a thigh with L was smaller than others (X:149.3±16.1, L:147.4±19.4, B:152.7±18.8). The passive drag with L was larger than others. The passive drag (N) with X and F were small at lower velocity but became larger at higher velocity (velocity 0.6-1.4m/s ; X:10.2±10.4, L:14.7±11.8, F:6.5±10.3, B:10.0±12.2, velocity 1.6-1.8m/s ; X:62.5±18.3, L:63.5±14.1, F:49.3±13.1, B:45.0±10.9). It was observed the legs f position with X or F became closer to the horizontal line. DISCUSSION: The results of passive drag reveal that rubber swimwears (X and F) indicated a different tendency between the lower and higher flow velocity. It is thought that the drag decreased due to the body position became close to the horizontal because the rubber swimwears might have an effect for lifting the legs, but the effect induced an increase of the wave drag at higher velocity, then the passive drag inverted between the rubber swimwears and others. For an effect of constriction by the swimwears, it was observed the CS of a thigh was decreased by wearing the L and X. As all findings of the research, it is concluded F has an effect for reducing the drag due to lift legs, L has an advantage to restrain vibration of legs by a strong compression, and X gets both benefits of the two swimwears. According to the new regulation, a rubber material was not forbidden. So it was important to investigate a new material instead of a rubber and to achieve an appropriate wearing pressure.